COVID-19 pandemic: a cross-sectional design of cases (Research, Society and Development, 2020)
Objective: To quantify the evolution of COVID-19 cases from the analysis of reports issued by the World Health Organization from January 21 to May 31, 2020. Methodology: This is a descriptive, bibliographic and documentary epidemiological study, built with secondary data obtained from the reports of the world evolution of SARS-CoV-2, from the World Health Organization, from the initial period of the disease outbreak until reaching the pandemic level. The data were analyzed, categorized and presented in 3 stages: 1) Identification of the new SARS-CoV-2 to the Chinese epicenter in decline; 2) New epicenter and dissemination of COVID-19 by regions; 3) Epicenter of the Region of the Americas. Results: From the identification of the new SARS-CoV-2 to the Chinese epicenter, an explosion of cases was  identified, initially in China, with several lethal outcomes in relation to confirmed cases. Then, several countries started to live with the reality of COVID-19, and the disease was declared a pandemic. Of the reported cases, several have progressed to serious illnesses including pneumonia and respiratory failure. Rapidly, the numbers of cases globally reached expressive marks. In Europe and America there was an increase in both new cases and deaths, especially in Brazil, while in China the number declined. Conclusion: In the present study it was possible to conclude that it is a serious disease, with a demand for strict and permanent sanitary control to reduce the potential for contamination. The analyzes show an accelerated spread of the virus with a negative outcome, a situation confirmed by the rapid expansion of the disease on all continents.